Effects of polystyrene sulfonate/graphene and Mn3O4/graphene on property of aluminum(zinc)-air batteries. (28th April 2020) - Ma, Jingling; Zhang, Yi; Qin, Conghui; Ren, Fengzhang; Wang, Guangxin
Abstract: A polystyrene sulfonate/graphene-based NaOH electrolyte and a Mn3 O4 /graphene catalyst were prepared for fabricating and testing metal-air batteries with pure Al and Zn anodes. Electrochemical performances, corrosion rates and surface morphologies were investigated. The operating voltage, anodic utilization rate and energy density of the assembled aluminum-air battery are 1.167 V, 88% and 2546 Wh·Kg −1, respectively. This overall performance is better than Al-air battery with 4 M NaOH solution and MnO2 catalyst. Apparently, polystyrene sodium sulfonate/graphene improves the conductivity of the solution and reduces the corrosion rate of aluminum anode, and Mn3 O4 /graphene reduces cathode polarization of air cathode. Highlights: Polystyrene sulfonate/graphene and Mn3 O4 /graphene improve battery performance. Mn3 O4 /graphene reduces the cathode polarization of the air cathode. In static state, polystyrene sulfonate/graphene inhibits corrosion rate of Al(Zn).